Experimental and kinetic study of the catalytic desorption of CO2 from CO2-loaded monoethanolamine (MEA) and blended monoethanolamine – Methyl-diethanolamine (MEA-MDEA) solutions. (15th July 2019) - Akachuku, Ananda; Osei, Priscilla Anima; Decardi-Nelson, Benjamin; Srisang, Wayuta; Pouryousefi, Fatima; Ibrahim, Hussameldin; Idem, Raphael
Abstract: The kinetics of catalyst-aided desorption of CO2 from CO2 -loaded MEA (5 mol/dm 3 ) and blended MEA-MDEA (7 mol/dm 3 ) solutions at CO2 loadings from 0.3 to 0.5 mol CO2 /mol amine were studied over a Lewis acid catalyst (γ-Al2 O3 ) and a Brønsted acid catalyst (H-ZSM-5) in an absorber–desorber CO2 capture bench-scale plant (columns of 0.051 m ID and height of 1.067 m) at temperatures of 348–368 K. The results showed that the conversion increases relative to no catalyst for MEA were 55 and 74% while for MEA-MDEA, they were 65 and 85.2% with γ-Al2 O3 and H-ZSM-5, respectively. A comprehensive mechanistic LHHW rate model was developed for the catalytic CO2 desorption process. Highlights: The overall kinetic performance is greatly affected by catalyst and solvent type. Solid acid catalyst in desorber even at below 100 °C increased CO2 conversion. Solid acid catalyst in desorber even at below 100 °C reduces the heat duty. For E A : MEA-MDEA(H-ZSM-5)< MEA-MDEA(γ-Al2 O3 ) < MEA(H-ZSM-5) < MEA(γ-Al2 O3 ). For kinetics, HZSM-5 decreased E A and γ-Al2 O3 increased the frequency factor.